Organization of the housing construction business by assessing the legal background - Mitkus, Sigitas; Cibulskienė, Renata (Business: Theory and Practice, 2011)
The article deals with legal relationship established in the housing construction business between the housing acquirer and the contractor or the investor. The legal environment of business is analyzed by highlighting the peculiarities, advantages and drawbacks of legal regulation of particular business organization methods. The article discusses both, business organization principles widely known to society such as construction outsourcing or sale-purchase, and less known, however capable of being useful in the current market situation cases of long-term lease or the establishment of housing association. A lot of attention is devoted to the rights protection mechanism of the natural person/housing acquirer as a consumer established in the laws and different business organization principles applicable to a different extent. The article pays special attention to the Lithuanian court practice on the issues analyzed. Article in Lithuanian. Būsto statybos verslo organizavimas įvertinant teisinę aplinką Santrauka. Straipsnyje nagrinėjami būsto statybos versle susiklostantys teisiniai santykiai tarp būsto įgijėjo ir rangovo arba investuotojo. Analizuojama būsto statybos verslo teisinė aplinka akcentuojant atskirų verslo organizavimo būdų teisinio reglamentavimo ypatumus bei privalumus ir trūkumus. Straipsnyje aptariami tiek verslo bendruomenei plačiai žinomi verslo organizavimo būdai, tokie kaip statybos ranga ar pirkimas–pardavimas, tiek mažiau žinomi, tačiau šiandienėje rinkos situacijoje galintys būti naudingi ilgalaikės nuomos ar namų statybos bendrijos steigimo atvejai. Daug dėmesio skiriama būsto įgijėjo fizinio asmens, kaip vartotojo, teisių apsaugos mechanizmui, įtvirtintam įstatymuose ir skirtinguose verslo organizavimo būduose taikomam skirtinga apimtimi. Straipsnyje atkreipiamas dėmesys į Lietuvos teismų praktiką analizuojamais klausimais. Reikšminiai žodžiai: būstas, statybos verslas, statybos ranga, pirkimas–pardavimas, ilgalaikė nuoma, bendrija.